Interface-engineered N, S-doped carbon dots embedded cerium metal-organic framework nanohybrid as a multifunctional electrode for the detection of mercury in environmental and biological matrices - Pandiyan, Pawel; Shankar, Ramya; Pushpa Malini, T. (Materials science & engineering. B, Solid-state materials for advanced technology, 2026)
Mercury pollution has increased primarily due to man-made activities, causing serious problems for all living organisms. This work describes a susceptible and selective electrochemical sensor designed to monitor the mercury level in fish samples using a novel carbon dot-embedded cerium metal-organic framework. The simple solvothermal method was employed to synthesize the Carbon dots (CD) embedded in Ce-TA nanopowders using terephthalic acid (TA) as an organic linker. The structural characterization of the prepared CD@Ce-TA was studied using various analytical techniques. The X-ray diffraction pattern of the material confirms the triclinic crystal structure of Cerium-Terephthalic acid (Ce-TA) MOF. The functional groups present in the MOF were analyzed by the FTIR spectrum analysis. The XPS analysis confirm the presence of nitrogen and sulfur in the hybrid material which confirms the N,S doped carbon dots formation. The CD@Ce-TA modified glassy carbon electrode (GCE) results in excellent efficiency for sensing mercury ions. The CD@Ce-TA/ GCE results with a LOD of 3 nM with an ultrahigh sensitivity of 26.98 μA nM−1 cm−2. Fish and lake water samples were used to test the sensor's practical use, and the findings demonstrated a good recovery percentage. This represents the first work of the Cerium-TA MOF modified with carbon dots on its surface, which enhances the sensitivity of the material through its sp2 carbon skeleton and heteroatoms like nitrogen, oxygen, and sulfur, which also enhances the electrocatalytic activity of the material. Thus, the lower detection limit goes up to the trace level of 3 nM. [Display omitted] •Carbon dots embedded in the Ce-TA metal-organic framework (CD@Ce-TA) were synthesized using a simple solvothermal method.•A sp2-hybridized carbon skeleton with N, S, and O heteroatoms has increased the sensitivity and adsorption performance.•CD@Ce-TA/GCE achieves an ultra-low LOD of 3nM for Hg²⁺, markedly surpassing the WHO standard of 30 nM safety benchmark.•The proposed sensor has shown an excellent sensitivity of 26.98 μA nM−1 cm−2.